Silicon alleviates ammonium toxicity in cauliflower and in broccoli - Ferreira Barreto, Rafael [UNESP]; Schiavon Júnior, Aparecido Alecio [UNESP]; Maggio, Marcos Aurélio [UNESP]; de Mello Prado, Renato [UNESP] (Elsevier, 2017)
Plant growth may be higher with a nitrate (NO3 −) and ammonium (NH4 +) ratio (N-A ratio), in relation to a particular form of N. However, the NH4 + can be toxic. In order to alleviate NH4 + toxicity in plants, silicon (Si) can be used. To evaluate the effect of N-A ratios and Si in cauliflower and broccoli, the plants were grown in hydroponic system, using coarse sand substrate. Randomized block design was used, with four replications, in a 3 × 2 factorial scheme, corresponding to total N concentration of 15 mmol L−1, with N-A ratios of 100/0, 50/50 and 0/100, in the absence and presence of Si (2 mmol L−1). The NH4 + source was ammonium chloride and as Si source, stabilized sodium and potassium silicate. The results suggest that in cauliflower, the alleviation of NH4 + toxicity using Si can be noticed through the increase of the physical integrity of the membranes and in broccoli, the alleviation of NH4 + toxicity is associated most with the water use efficiency. Si alleviates NH4 + toxicity in cauliflower when the total N concentration is 15 mmol L−1 and 50% is supplied in the form of NH4 +. In broccoli, Si improves the effect of NO3 − and alleviates NH4 + toxicity.
Keywords: Abiotic stress; Beneficial element; Brassica oleracea; NO3 −/NH4 + ratios; Nutrient solution